Perspectives on Political Communication in Africa
XXIII, 272 p. 12 illus.
Keywords: This edited collection is a cutting-edge volume that reframes political communication from an African perspective. Focusing on African countries such as Mozambique, Zambia, Rwanda, Zimbabwe, Ghana, Kenya, Uganda, South Africa, Ivory Coast and Nigeria and occasionally drawing comparisons with other regions of the world, this book critically addresses the development of the field focusing on the current opportunities and challenges within the African context. By using a wide variety of case studies, this collection gives space to previously understudied regions of Africa and challenges the over-reliance of western scholarship on political communication on the continent.